Preservation of Traditional Cultural Heritage by the Cilacap Regency Education and Culture Office - Ida Noviyanti; Dini Yuliani; Otong Husni Taufiq (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Traditional cultural heritage is an important part of a region's identity and character, yet its preservation faces various challenges amidst modernization and globalization. This study aims to analyze the strategies implemented by the Cilacap Regency Education and Culture Office in preserving traditional cultural heritage. This research employed qualitative methods with a descriptive approach. The primary data sources were obtained through in-depth interviews with key informants consisting of office officials, cultural practitioners, and relevant community leaders. Additional data were obtained through direct observation and documentation studies of official office documents. Data analysis techniques included data reduction, data presentation, and thematic drawing of conclusions based on Fred R. David's strategic management theory. The results indicate that the preservation strategy has been systematically designed in the Regional Cultural Principles (PPKD), Strategic Plan (Renstra), and Medium-Term Development Plan (RPJMD). However, program implementation has been uneven and remains focused on specific areas. Key obstacles include limited cultural data, human resources, infrastructure, and low community participation. The office has implemented several improvement efforts through data updates, cross-sectoral collaboration, and participatory activities. In conclusion, the strategy has a planned direction, but strengthening is needed in the equitable implementation and sustainability of cultural preservation programs.